Absurdism in The Adam Project (2022) film - Catherine Morgan (Universitas Negeri Surabaya, 2026)
In a world that moves forward without offering answers, humans still persist in their search for meaning. Albert Camus’ philosophy of absurdism is born from this dissonance the confrontation between human longing for clarity and the universe’s unwavering silence. The Adam Project (2022) presents more than a sci-fi adventure; it unfolds as a meditation on grief, alienation, and the futile yet deeply human desire to control time and fate. Using film study and Camus’ absurdist lens, this research explores how absurdism materializes through narrative, visuals, and the characters’ existential responses. Adam, both young and old, embodies the absurd hero: defiant yet wounded, sarcastic yet sincere, constantly questioning within a universe that offers none. As Camus writes, “One must imagine Sisyphus happy”and this film quietly echoes that sentiment. In a chaotic world governed by an indifferent universe, meaning is not found, but made. The Adam Project thus becomes not just a cinematic text, but a philosophical mirror: revealing how absurdism is not a surrender to despair, but a choice to live meaningfully in spite of it.